2020
DOI: 10.1101/2020.10.07.20187641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two-tiered SARS-CoV-2 seroconversion screening in the Netherlands and stability of nucleocapsid, spike protein domain 1 and neutralizing antibodies

Abstract: Serological testing in the COVID-19 pandemic is mainly implemented to gain sero-epidemiological data, but can also retrospectively inform about suspected SARS-CoV-2 infection. We verified and applied a two-tiered testing strategy combining a SARS-CoV-2 receptor-binding domain (RBD)-specific lateral flow assay (LFA) with a nucleocapsid protein (NCP) IgG ELISA to assess seroconversion in n=7241 individuals. The majority had experienced symptoms consistent with COVID-19, but had no access to RT-PCR testing. Longi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…In agreement with this hypothesis, correlation between neutralization and RBD and S1 IgG levels, measured by Luminex assay, showed slightly higher coefficients and lower pvalues at 10 weeks PO than at 6 weeks PO (Figure 2C). Similarly, Garritsen et al found higher stability of sera neutralizing antibody as compared to S1 IgG levels in two tests performed separated 46 -96 days, at various times after infection (34). However, other studies have found a decline in neutralizing antibodies at times after exposure that were similar to this study (10,24) which could be attributed to different study populations and clinical differences.…”
Section: Discussionsupporting
confidence: 64%
“…In agreement with this hypothesis, correlation between neutralization and RBD and S1 IgG levels, measured by Luminex assay, showed slightly higher coefficients and lower pvalues at 10 weeks PO than at 6 weeks PO (Figure 2C). Similarly, Garritsen et al found higher stability of sera neutralizing antibody as compared to S1 IgG levels in two tests performed separated 46 -96 days, at various times after infection (34). However, other studies have found a decline in neutralizing antibodies at times after exposure that were similar to this study (10,24) which could be attributed to different study populations and clinical differences.…”
Section: Discussionsupporting
confidence: 64%
“…Independently of the disease trajectory, the majority of acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections trigger a response of the adaptive immune system [2][3][4] . Essential for this immune response are antibodies that neutralize SARS-CoV-2 (NAbs) by preventing virus binding to the host-cell receptor angiotensin-converting enzyme 2 (ACE2) [5][6][7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to consider that here we analyzed samples from individuals who presented mild symptoms and were fully recovered, which may explain the lower incidence observed for some immunoglobulin isotypes, as antibody titers strongly correlates with disease severity [42,43,44]. Indeed, studies performed with hospitalized patients have reported up to 94% seroconversion of against N protein [45,46,47].…”
Section: Discussionmentioning
confidence: 99%